Atividade antioxidante de extrato de Açaí de Juçara (Euterpe edulis Mart.) e aplicação em iogurtes - Borges, Giulia Caroline de Cristo (2018)
The search for a healthy diet has shown an increase in the consumption of foods that have in their chemical composition elements that bring health benefits. As an example of these foods we can mention Açaí de Juçara (Euterpe edulis Mart.) And also yoghurts, which show high beneficial power to the consumers. The formulation of yogurt plus Açaí de Juçara may present itself as a healthy and tasty alternative. The objective of the present work was to quantify the bioactive compounds present in the Açaí de Juçara extract, to elaborate Açaí de Juçara yoghurt formulations, to evaluate the lipid oxidation during the 28 days after its production and the sensorial acceptance of the product. The quantification of the total phenolics was performed by Folin-Ciocateau methodology, the quantification of total anthocyanins was performed by means of pH difference and the antioxidant activity was evaluated by means of three different methodologies sequestration of the radical DPPH, sequestration of the radical ABTS and FRAP. Lipid oxidation was analyzed using the TBARS methodology (2-thiobarbituric acid reactive substances). Sensory acceptance was evaluated by 77 untrained judges by means of ordering tests and by hedonic scale of 9 points.The extract of Açaí de Juçara presented total phenolic compounds content equal to 56.26 mg EAG.g-1, total anthocyanins content equal to 265.26 mg.100 g-1 and showed antioxidant activity equal to 128.6 mmol of Trolox. g-1 by the DPPH methodology, 2.79 mmol of Trolox.g-1 by the ABTS methodology and 135.47 μmol Fe2 + .g-1 by the FRAP methodology.Yogurt formulations were highly accepted, higher than 80%. It is concluded that the extract of Açaí de Juçara has a high content of total phenolic compounds, total anthocyanins and presents high antioxidant activity, proving to be an excellent alternative for application in the most diverse formulations.